Respuesta :

Answer:

formula: y-y1 = m(x-x1)

Step-by-step explanation:

General:

1. find 2 points directly on the line and apply the formula y2-y1 over x2-x1 this answer equals m

2. then add it into the formula y-y1 = m(x-x1) remember x and y are variables so only put numbers in y1 and x1

3. solve the problem

Example:

line 1:

1. y2-y1 over x2-x1 is 4-6 over 6-4 = -1

2.  y-6 = -1(x-(-4) or y-6 = -1(x+4)

3. y-6 = -1x-4

4. y = -1x-2

3. the gradient equals: y = -1x-2

Hope this helps :) Let me know if you need a better example

Otras preguntas